Sosialisasi Perda Kota Banjarmasin Nomor 7 Tahun 2013 Tentang Kawasan Tanpa Rokok - Dewi Merdayanty; Junaidi Junaidi; Agus Humaidi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Banjarmasin City Regional Regulations Concerning Non-Smoking Areas is a rule made by the Government to reduce violations committed by the community, but in reality there are still many who violate these rules. In this service activity, we discuss the effectiveness and factors that occur in the field. This activity focuses on two problem formulations, namely, how effective is the Banjarmasin City regional regulation Number 7 of 2013 concerning non-smoking areas in university areas in Banjarmasin, what are the factors that influence the effectiveness of Banjarmasin City regional regulation Number 7 of 2013 concerning non-smoking areas.